Design for green lean six sigma to improve sustainability in the pharmaceutical industry – a case study - Yvonne McGlinchey; Javed Iqbal; Anna Trubetskaya; M Thenarasu; Olivia McDermott (Production and Manufacturing Research: An Open Access Journal)
This paper’s purpose is to outline the use of the Design for Green Lean Six Sigma (DFGLSS) to evaluate bulk pharmaceutical product packaging and ascertain a path to its reduction and even elimination to improve an organisation’s sustainability. The methodology employed was DFGLSS using the Define, Measure, Analyse, Design and Verify steps. The packaging type responsible for the highest sustainability impact was identified and replaced, resulting in a decrease in overall carbon emissions associated with packaging. Adopting a reuse strategy for this packaging type resulted in cost savings, further reductions in carbon emissions, and in the total weight of bulk packaging waste. This study is one of the first, to the author’s knowledge, to apply DFGLSS within a pharmaceutical organisation or elsewhere and within the wider academic literature to improve sustainability. Thus, it contributes to a research gap by demonstrating how DFGLSS can be successfully applied to promote sustainability in pharmaceutical packaging and product packaging in general.